The complete mitochondrial genome and phylogenetic analysis of Upogebia major (De Haan, 1841) - Xiaoyue Sun; Jun He (Mitochondrial DNA. Part B. Resources, 2021)
The complete mitochondrial (mt) genome of Upogebia major (De Haan, 1841) is 16,131 bp in length, comprising 13 protein-coding genes (PCGs), 22 transfer RNA genes, and two ribosomal RNA genes. The nucleotide composition for U. major is 34.3% of A, 36.6% of T, 10.9% of C, and 18.3% of G. All PCGs are initiated by ATN codons, except for the cox1 gene, which was not determined. Nine PCGs use a common stop codon of TAA or TAG, the other four end with an incomplete stop codon (a single stop nucleotide T). Phylogenetic tree analysis showed that U. major had a close relationship with the species from the family Thalassinidae. The study will provide an important theoretical basis for further analysis of mt genome evolution and the phylogenetic relationships of the order Decapoda.